Selección del zooplancton por el charal Chirostoma jordani (Atheriniformes: Atherinidae) - Navarrete, Norma A (1996)
Zooplankton selectivity by the silverside fish Chirostoma jordani, was made in the Trinidad Fabela reserveir, México (19° 48 ' 12"- 50' 36" N; 99° 46' 23" - 39" W) encompassing the four seasons (1983 - 1984). Fish were collected using a dragnet with 8 mm mesh size and zooplankton with a 125 micron mesh size pJankton neto The zooplankton community is represented by six genera among which Diaptomus was the most abundant throughout the year. The silverside select their prey, prefering the genera Bosmina, Daphnia and Diaptomus.